2019
DOI: 10.1161/strokeaha.119.024950
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations in the First 24/7 Mobile Stroke Unit

Abstract: Background and Purpose— Mobile Stroke Units (MSUs) provide innovative prehospital stroke care but their 24/7 operation has not been studied. Our study investigates 24/7 MSU diurnal variations related to transport frequency, patient characteristics, and stroke treatments. Methods— We compared transportation frequency, demographics, thrombolytic and mechanical thrombectomy administration, and treatment metrics across 8-hour shifts (morning, evening, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…The operational hours were designed to capture approximately 64% of all suspected stroke dispatches within the 20-kilometre primary co-dispatch radius, whilst simultaneously being able to be broken into two 5 h morning and afternoon shifts. The estimated workload appears to be consistent with the experience of the first 24 h MSU based in Toledo, USA where the vast majority of dispatches occurred from 7AM-7PM and the bulk of the thrombolysis cases occurred between approximately 10AM-6PM [6] .…”
Section: Operationalization Of the Melbourne Mobile Stroke Unitsupporting
confidence: 74%
“…The operational hours were designed to capture approximately 64% of all suspected stroke dispatches within the 20-kilometre primary co-dispatch radius, whilst simultaneously being able to be broken into two 5 h morning and afternoon shifts. The estimated workload appears to be consistent with the experience of the first 24 h MSU based in Toledo, USA where the vast majority of dispatches occurred from 7AM-7PM and the bulk of the thrombolysis cases occurred between approximately 10AM-6PM [6] .…”
Section: Operationalization Of the Melbourne Mobile Stroke Unitsupporting
confidence: 74%
“…The pooled average rate was 2.0% (95% CI 1.2–2.8%). Eleven studies reported information regarding rates of tPA administration based on time of MSU availability ( 4 , 5 , 8 , 9 , 13 16 , 18 , 20 , 21 ). Collectively, tPA was administered 1,858 times over 4,961 available days (defined as 24-h period), for a rate of 0.358 (95% CI 0.215–0.502) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…While mobile stroke units gain increasing popularity, concerns regarding its cost‐effectiveness and wide‐scale implementation remain. Zaidat et al 15 demonstrated that 91% of intravenous tissue plasminogen activator administrations on the mobile stroke unit occurred between the hours of 7:00 am and 11:00 pm . The RACE score and other prehospital stroke triage tools may effectively complement mobile stroke units at night and allow for early, accurate identification and treatment of LVO.…”
Section: Discussionmentioning
confidence: 99%